MAKNA LAFADZ IDRIB DALAM QS. AN-NISA AYAT 34 PERSPEKTIF ULAMA KABUPATEN MALANG - Haris, Muhammad Lukman (Fakultas Syariah, 2014)
The background of this research, is the fact often indicates that the marital relationship is not always harmonious. Sometimes a spouse fails to save the Big Dipper in the household as it faces problems that are considered to be beyond their means. Sometimes women ignore or less than the maximum husband right in doing his duty to the house and her children. This study aims to describe, how do cleric Malang Meaning Lafadz idrib on Qs. An-Nisa verse 34 and how do Malang cleric on how the settlement of disputes in domestic life which in turn can realize harmonious family. While the object of research is the Ulema Malang.The results of this Penetian, researchers finally, first, the meanings of the Salafi Ulama Lafadz idrib on Qs. AnNisa verse 34 by taking the path of violence that is hitting with the hand, while the scholars of Modern and Contemporary in meaning Lafadz Idrib ie, hit without using street violence, ie by continuously advised. Second, Salafi cleric in resolving disputes in domestic life are clubbed, Salaf allow wife beating wives who disobey the reason is still the responsibility of the husband, it is necessary to resort to violence to revive him. Modern and contemporary scholars While there are two methods to resolve disputes that occur in the home, The first is by way of violence, that is allowed to beat his wife as long as the stage-the stage prior to the beating had done well and has not produced results. The second dispute resolution process in the household is, without the use of the least violent way, which is enough to be kept advised menurus due to violence if the problem is not going to finish, and beating only produces more dangerous uprising.Studinya bertujuan untuk menggambarkan, bagaimana ulama Malang Arti Lafadz idrib pada Qs. An-Nisa ayat 34 dan bagaimana ulama Malang tentang bagaimana penyelesaian sengketa dalam kehidupan rumah tangga yang pada gilirannya dapat mewujudkan keluarga yang harmonis. Sedangkan objek penelitian adalah Ulama Malang. Hasil Penetian ini, peneliti akhirnya, pertama, arti dari Salafi Ulam aLafadzidrib pada Qs.An - Nisa ayat 34 dengan mengambil jalan kekerasan yang memukul dengan tangan, sementara para ulama Modern dan Kontemporer dalam arti Lafadz Idribi adalah memukul tanpa menggunakan jalan kekerasan, yaitu dengan saran atau masukan, kedua, ulama salafi dalam menyelesaikan sengketa kehidupan rumah tangga dengan dipukul, ulama’ Salafi membolehkan pemukulan terhadap istri yang tidak taat alasannya adalah karena masih tanggung jawab suami, maka perlu menggunakan kekerasan untuk menghidupkan kembali kepadanya. Sedangkan para ulama’ kontemporer pertama adalah dengan cara pendekatan musyawarah, apabila belum membuahkan hasil. Proses penyelesaian sengketa kedua dalam rumah tangga adalah dengan peringatan yang keras, hindari kekerasan karena hanya menghasilkan pemberontakan lebih berbahaya.